(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
The aim of this paper is to discuss poverty in rural areas. We intend to bring the discussion to a tangent with the dimensions of poverty characterization, with the specificities of rural poverty in Brazil and its manifestation in the micro-region of Cruzeiro do Sul - Acre. The approach uses different indicators of poverty and supports the debate in theoretical reflections built on bibliographical study and documentary research, which are protected by the qualitative approach. The bibliographic research includes consulting academic productions in journal databases and thesis and dissertation databases. Documentary research consisted of analyzing documents from official bodies and legislation on the subject. The data refers to the characterization of poverty in rural areas in the Cruzeiro do Sul micro-region, which is made up of five municipalities in the state of Acre. It shows that impoverishment cannot be understood as an isolated phenomenon, as it is shaped by unequal development processes in which rural areas reproduce a unique reality, which in the context studied is characterized by Amazonian social and environmental specificities.